Application of mathematical models for MALDI-TOF MS on the example of Dirofilariasis. (March 2022) - Nagorny, S.; Aleshukina, A.; Aleshukina, I.; Denisenko, V.; Ermakova, L.; Pshenichnaya, N.
Abstract : Purpose: Diagnosis of human tissue helminthiasis remains a difficult problem in practice. The investigation for alternative direct methods of verification is an important area of laboratory diagnostics.. MALDI-TOF MS has high diagnostic accuracy, speed of examination and minimal labor costs, but requires the presence of reference protein profiles of pathogens. Therefore, the search for ways to create protein profiles of parasitic pathogens is relevant. To assess the feasibility of using mathematical modeling to optimize the MALDI-TOF MS method in identifying helminths using the example of Dirofilaria immitis, Dirofilaria repens. Methods & Materials: We used 5 female D.repens that were removed from sick people and 5 D. immitis - from the heart of one dog. Sample preparation of biological material (head ends of nematodes) was carried out according to the original author's method. Mass spectr profiles of homogenized products were obtained using the Sepsityper Kit 50 (Bruker Daltonics) with FlexControl software (Bruker Daltonics). Visualization was performed with Flex analysis software (Bruker Daltonics). The preliminary processing of mass spectra was carried out using the MALDI quant package. The R software environment was used to create a mathematical model Results: Analysis of protein extracts in FlexControl software (Bruker Daltonics) revealed reproducible spectra with high-intensity peaks in the range from 2 to 20 kDa. The spectrum of proteins of D. immitis reliably showed peaks in the m / z range from 8600 to 10400 kDa, in the spectra of D. repens - a peak at 11400 kDa. Using the MALDI quant package in the R software environment, the mass spectra of both nematodes were averaged. The resulting clusters in dendrograms showed that in D. immitis samples the coincidence rate was 100%, in D. repens samples - 70% possibly due to phenotypic differences in D. repens removed from different patients, while species D. immitis were isolated from one animal. Conclusion: The obtained results of processing the mass spectra in the R - MALDI quant software environment will make it possible to replenish the library of reference protein profiles of nematodes of the genus Dirofilaria for their reliable identification.